Monoclonal Antibodies and Their Functional Fragments in Research, Diagnosis and Therapy 2.0 - Ruvo, Menotti; Sandomenico, Annamaria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Monoclonal antibodies (mAbs) are among the most specialised molecules for the recognition and capture of specific analytes. Hundreds of thousands of mAbs have been generated for a large number of different antigens with increasing affinity and specificity and are available for the most diverse purposes. Many of them have been validated as irreplaceable agents for diagnosis and therapy or as unique reagents for research. Others have been developed using emerging technologies that avoid the need for animal immunisation. This short book strives to gather the perspective view of the various contributing authors and to survey the new strategic assets adopted to generate novel monoclonal antibodies or surrogates, such as Fab, Fab2, ScFv and nanobodies, which have an increasing impact in biomedicine as therapeutic or diagnostic assets in various diseases.